An industry‐oriented strategy for the finite element simulation of paperboard creasing and folding. Issue 6 (4th April 2017) - Domaneschi, Marco; Perego, Umberto; Borgqvist, Eric; Borsari, Roberto
Abstract : The numerical simulation of paperboard creasing and folding processes is of increasing importance for the design and production of safe and reliable packaging systems. The extreme material anisotropy and the complexity of these processes require however simulation capabilities which are seldom available in commercial codes. Several approaches have been proposed in the literature over the years, in most cases making use of non‐linear material models developed ad hoc for this purpose. These models, some of which are very effective and accurate, are not in general available in commercial codes and are often based on the definition of a large number of parameters. In this paper, the possibility to obtain acceptable, first‐hand simulation results using only features already available in a commercial code is investigated. An advanced continuum constitutive model, recently presented in the literature, has been used as a reference for tuning the model and for assessing its accuracy. It is shown how standard features, usually available in state‐of‐the‐art commercial codes, can be employed to deal with the extreme material anisotropy, obtaining qualitatively good results in both the creasing and folding phases. The used standard model accounts for the extremely high anisotropy by means of embedded shell elements, playing the role of reinforcements in the fibre direction. The matrix is assumed to be isotropic and elastoplastic, with properties determined based on the behaviour in the thickness direction. The adopted plasticity model is a modified Drucker–Prager model with a cutoff on the tensile pressure side, available in the used commercial code. The procedure adopted for the identification of the small number of required material parameters is also discussed. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A finite element model for the simulation of paperboard creasing and folding, based on standard features available in a multipurpose finite element code, is proposed as an analysis tool for the definition of a safe parameters space in industrial applications. The paperboard extreme anisotropy is accounted for by means of shell elements, embedded in the 3D elastoplastic mesh and used as in‐plane reinforcements. The strategy employed for the model parameters identification is critically discussed, and the model is verified against a reference, recently published approach.